(3aVGFd TgQ TYHGfs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3MOKfG CHj QMeg Gddg Yf CMeO Hf EOQjS bGd MOKfG eMeO Hf YjSi Hf YHjO Yf jhfS Hf YHO GdQMef Yf YHO Gddg Hf GdaVd GdgGTej Yf GdUGOb LYaQ Hf eMeO YdjgeG GdSdGe (B....s
(3BNQgG (B:s
..(3Yf CHj SdeI Hf YHO GdQMef Yf YGFTI RhLI GdfHj Udi Gddg Ydjg hBdg , bGdJ eG QCjJ QShd Gddg Udi Gddg Ydjg hBdg aj TgQ CcKQ UjGeG efg aj TYHGf Jes
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj Yf fSNI Yf fSNI Yf fSNI HNW GdeUfas
(3JHUQI GdYfhGf (B:s
(3Ydi WQI GdQSGdI HNW GdeUfa (B: (3PcQ GdeUfa gPG GdcJGH aj BNQ HGH KhGH Uhe TYHGf aj cJGHg eG dG jMVQg Gdabjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \274s
(3GdPQjYI (B16 - 178 ( 1012 )s
Keywords: (3GdMOjK hGdeUWdMs